The mineralogy and geochemistry of the Rooikoppies iron-rich ultramafic pegmatite body, Karee Mine, Bushveld Complex, South Africa - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.